Adaptive Modulation Scheme Based on Partially Pre-Distorted LACO-OFDM for VLC System - Yaqi Sun; Fang Yang (IEEE Photonics Journal, 2019)
In this paper, an adaptive modulation scheme for visible light communication (VLC) system based on partially pre-distorted layered asymmetrically clipped optical orthogonal frequency division multiplexing (LACO-OFDM) is proposed. The clipping noise that falls on the higher layers in the conventional LACO-OFDM results in inter layer interference, which can be eliminated by the operation of pre-distortion at the expense of extra power consumption. The proposed partially pre-distorted scheme makes a tradeoff between error propagation and power cost to suit different transmission environments. The probability distribution functions of the conventional and pre-distorted LACO-OFDM schemes are analyzed and compared and the layers that should be pre-distorted in the proposed scheme is decided adaptively by maximizing the achievable rate. The computational complexity of the proposed scheme is also investigated, which is acceptable compared with the previous schemes. Simulation results show that the proposed scheme has a superior bit error rate performance compared with the conventional and pre-distorted LACO-OFDM schemes.